Clinical and angiographic outcomes following percutaneous treatment of non-occlusive vs. chronically total occluded coronary lesions. (3rd October 2022) - Aytekin, A; Cassese, S; Kufner, S; Ndrepepa, G; Voll, F; Rheude, T; Seguchi, M; Coughlan, J J; Pinieck, S; Joner, M; Fusaro, M; Kastrati, A; et al.
Abstract: Background: Recent advancements in recanalization techniques, introduction of dedicated equipment and elaboration of systematic algorithmic approaches have significantly improved procedural success of coronary chronic total occlusion (CTO) percutaneous coronary intervention (PCI) procedures. However, despite their undisputable merits in terms of procedural success, direct comparisons of mid-term clinical and angiographic outcomes following CTO and non-CTO-PCI are missing. Purpose: The aim of this study was to assess the clinical and angiographic outcomes of patients undergoing successful CTO-PCI as compared to a propensity matched cohort of patients undergoing PCI of non-occlusive coronary lesions. Methods: All consecutive patients undergoing successful CTO recanalization procedures at our center between 2015 and 2018 were included (N=453; 472 lesions). For matching purposes, all patients undergoing non-CTO-PCI present in our database were included (N=14733; 23458 lesions). A 1-to-1 nearest neighbour matching using baseline clinical and angiographic variables was performed to identify one patient undergoing non-CTO-PCI (N=453; 472 vessels) for each patient undergoing CTO-PCI (N=453; 472 vessels). Surveillance angiography was scheduled at 6–9 months and clinical follow-up was performed up to 12 months. The primary clinical endpoint of interest was the incidence of major adverse cardiovascular events (MACE), a composite of all-cause death, myocardial infarction (MI) and target lesion revascularization (TLR). The secondary angiographic endpoint was in-segment binary restenosis. Results: Patients undergoing CTO-PCI displayed a tendency towards higher degrees of binary restenosis at surveillance angiography as compared to those undergoing non-CTO-PCI (CTO vs. non-CTO: 30.5% vs. 24.0%; P=0.058), despite not meeting statistical significance. Of note, the incidence of occlusive restenosis was low and comparable between groups (2.2% vs. 1.4%; P=0.603). At 12 months follow-up, MACE occurred in 83 patients (19.7%) in the CTO-PCI and 59 patients (14.1%) in the non-CTO-PCI group (hazard ratio [HR] = 1.44; 95% confidence interval [CI]: 1.03–2.01; P=0.033). TLR rates were significantly higher following CTO- as compared to non-CTO-PCI (17.2% vs. 10.3%; HR=1.72 [1.18–2.51], P=0.005). The incidence of all-cause death (2.6% vs. 3.3%; P=0.548) and MI (0.5% vs. 1.4%; P=0.177) was not significantly different between the groups. Conclusion: In this large, propensity-matched comparison of clinical and angiographic outcomes following CTO- vs. non-CTO-PCI, we found CTO-PCI to be associated with a higher MACE rate at 12 months, primarily driven by significantly higher TLR rates. The incidence of occlusive restenosis was low and comparable between groups. Funding Acknowledgement: Type of funding sources: None.